Minimum Wages and Social Policy : Lessons from Developing Countries - Cunningham, Wendy (Washington, DC: World Bank, 2012)
This report examines how minimum wages affect the income poverty of workers, their households, and the state. It does not question whether or not the minimum wage is a good policy: instead, it focuses on the tradeoffs in setting the minimum wage level. It takes as a starting point the literature on the wage and employment effects of minimum wages in Latin America and expands the discussion in three ways. First, the household is placed at the center of the debate. Poverty and inequality are measured at the level of the household, rather than at the individual level, to allow for employment and wage trade-offs among individuals who pool their income. Second, new research is presented on how the minimum wage affects groups whose labor market participation and success is considered "vulnerable": that is, youth, women, the low-skilled, and informal sector workers. Third, the implications of the minimum wage on wage and social expenditures of the government are measured. In the end, the report argues that the minimum wage by itself is not a sufficient tool for protecting the income of the poorest households, and that other social protection tools are necessary to complement it. The report has eight sections following the introduction. Chapter 2 presents a history of the minimum wage in LAC, the theory behind the functioning of the minimum wage, and empirical evidence from the OECD to lay a foundation for the Latin American experience. Chapter 3 presents an overview of the minimum wage in the Region, including a discussion of the definition of a minimum wage, institutional design, and who earns it. Chapter 4 focuses on the worker; it summarizes the existing literature, presents new evidence on the wage and employment effects of a minimum wage, and gives special attention to "vulnerable" labor market groups. Chapter 5 turns its attention to the household and presents the new (and only) evidence on the effects of the minimum wage on household poverty and inequality in LAC. Chapter 6 considers the state and discusses the cost of minimum wages to the government. Chapter 7 opens the discussion to the rest of the world and considers the lessons learned in other countries about setting, managing, and enforcing the minimum wage. Finally, chapter 8 concludes and presents policy considerations.